PEMANFAATAN ANTIOKSIDAN DARI EKSTRAK KULIT MANGGIS UNTUK MENGATASI DAMPAK CEKAMAN SALINITAS PADA KEDELAI YANG DIINOKULASI FUNGI MIKORIZA ARBUSKULA - Maman Suryaman; Darul Zumani (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2020)
Soybean production can be increased through extensification and marginal land becomes inevitable to be used due to the decrease of productive land. Plants grown on marginal soil, especially saline soils, show abnormal growth due to oxidative damages causes yield decrease even death of the plants. The objectives was to study invigoration technique using natural antioxidant and mycorrhizal fungi to increase soybeans tolerance under salinity stress. The research used factorial randomized block design. The first factor was salinity stress (0 and 1 % (w/v) NaCl concentration), the second factor was natural antioxidant (0, 1, 1.5, and 2% mangosteen peel extracts), and the third factor was arbuscular mycorrhizal fungi, 0 and 1g/polybag. The research was replicated three times. The variables were plant height, number of leaves, leave area, chlorophyl content, yield components and yield of soybean. The data was analyzed with Anova and Duncan’s multiple range test at 5% significant level. The conclusion was that salinity stress inhibited plant growth, yield components and yield of soybean. The application of arbuscular mycorrhizal fungi decreased the negative impact of salinity on vegetative growth, yield components and yield of soybean. The application of 2% mangosteen peel extract gave good effect on vegetative growth, yield components and yield of soybean under salinity stress.